Reservoir characteristics and palaeo-depositional environment of duski field, onshore, Niger- Delta, Nigeria (2016)
The Niger Delta is a prolific hydrocarbon producing belt in the southern Nigeria sedimentary basin on the continental margin of the Gulf of Guinea. This study used well log suites to delineate the hydrocarbon reservoirs, depositional environments and lithostratigraphy of the Duski Field, Onshore Niger Delta, Nigeria. A comprehensive interpretation of the three wells revealed five (5) reservoir units with low volume of shale and thickness variations between 24m and 60.20m. The average porosity values ranged from 12% to 34%, with high hydrocarbon saturation in all the reservoir sands. Generally, porosity and permeability values decrease with depth in all the wells. Cross-plots of water saturation (Sw) and porosity (ø) (Buckles plot) revealed that some reservoirs were at irreducible water saturation; hence producing water-free hydrocarbons. Therefore the hydrocarbon accumulation of this field is commercially viable and promising. This study revealed that the reservoir sand units were deposited within marginal marine depositional environment which include fluvial channel, transgressive marine, progradational and deltaic settings.